Case Report: Two Cases of Metastatic Pancreatoblastoma in Adults: Efficacy of Folfirinox and Implication of the Wnt/β-Catenin Pathway in Genomic Analysis - Raoul, Jean-Luc; Oziel-Taieb, Sandrine; Lecomte, Thierry; Adelaide, José; Guille, Arnaud; Chaffanet, Max; Poizat, Flora; Heymann, Marie-Françoise; Barbier, Louise; Bertucci, François (Frontiers in Oncology, 2021)
Pancreatoblastomas are uncommon tumors usually found in children. We report on two cases of metastatic pancreatoblastomas observed in young women. Systemic chemotherapy (FOLFIRINOX regimen) was associated with disease control in one case and partial response in the other, with improved general status for both. High-throughput sequencing of the tumor, twice identified alterations in the Wnt/β-catenin pathway: a CTNNB1 (S37C, exon 3) mutation in the first case and a breakage targeting APC (5q21–q22) in the second.